Use of Molecular Assays in Diagnosis and Monitoring of Cytomegalovirus Disease following Renal Transplantation - Aitken, Celia (American Society for Microbiology, 1999)
We compared two commercial molecular assays (the Murex Hybrid Capture CMV DNA assay [HCA], version 2, and the Roche Amplicor plasma PCR assay) with a standard shell vial assay in detecting and predicting cytomegalovirus (CMV) disease in a group of renal transplant patients and assessed the role of viral load measurements (using the HCA) in their management. The sensitivity of the HCA and Amplicor assay in terms of disease detection was 100%, compared to 71% for the shell vial assay. Both the HCA and the PCR assay detected all cases of disease, at medians of 11 and 12.5 days before the onset of symptoms, respectively. Significantly higher viral loads were detected in those patients with symptoms (7.9 × 10(5) copies/ml) than in patients without symptoms (7.9 × 10(4) copies/ml; P < 0.0001). There was also a trend towards higher viral loads in those patients with primary infections (7.8 × 10(5) copies/ml) than in those patients with reactivations of CMV disease or reinfections. Successful treatment with ganciclovir was associated with a >90% reduction in viral load. Both of these new assays are sensitive and easy to use. A comparison of accurate quantitation is also useful in monitoring responses to antiviral therapy.